Investigating the role of reducing agents on mechanosynthesis of Au nanoparticles. Issue 38 (5th August 2020) - de Oliveira, Paulo F. M.; Michalchuk, Adam A. L.; Marquardt, Julien; Feiler, Torvid; Prinz, Carsten; Torresi, Roberto M.; Camargo, Pedro H. C.; Emmerling, Franziska
Abstract : The influence of reducing agents on the mechanochemical synthesis of Au nanoparticles differ significantly from analogous solution syntheses. Environmentally benign mechanochemical syntheses of metal nanoparticles therefore require dedicated studies. Abstract : Control over the bottom up synthesis of metal nanoparticles (NP) depends on many experimental factors, including the choice of stabilising and reducing agents. By selectively manipulating these species, it is possible to control NP characteristics through solution-phase synthesis strategies. It is not known, however, whether NPs produced from mechanochemical syntheses are governed by the same rules. Using the Au NPs mechanosynthesis as a model system, we investigate how a series of common reducing agents affect both the reduction kinetics and size of Au NPs. It is shown that the relative effects of reducing agents on mechanochemical NP synthesis differ significantly from their role in analogous solution-phase reactions. Hence, strategies developed for control over NP growth in solution are not directly transferrable to environmentally benign mechanochemical approaches. This work demonstrates a clear need for dedicated, systematic studies on NP mechanosynthesis.